Sound Design for Electric Vehicles: Enhancing Safety and User Experience Through Acoustic Vehicle Alerting System (AVAS) - Ana Raquel Rodrigues Ferraz Esteves (2024)
The increasing use of electric vehicles has resulted in significant changes in car design, particularly in response to the absence of traditional combustion engine sounds. This shift has necessitated innovations to enhance pedestrian safety and improve user experience. This dissertation explores the current state of research and development in sound design for electric vehicles, focusing on implementing Acoustic Vehicle Alerting Systems (AVAS). Through a thorough literature review, the study explores vital concepts related to sonification, human-machine interaction, sound design, automation engineering, and environmental considerations such as urban soundscape management, ecological sustainability, and noise pollution. Existing AVAS systems are analyzed to identify common approaches, assess their effectiveness, and explore the potential for improvement. Additionally, the study delves into the characteristics of lo-fi and hi-fi soundscapes to determine the most suitable sounds for optimizing AVAS, aligning them with pedestrian safety and environmental goals. The practical component of the research involved designing AVAS prototypes using specialized software tools, including Ableton Live and Wwise Automotive. These sounds were integrated into simulated driving scenarios in Unity to test their performance and determine user preferences and their impact on pedestrian safety and user experience. The study offers valuable insights for designing AVAS by balancing safety, user satisfaction, and minimal environmental disruption. Participants preferred discrete, smooth, nature-like, melodic sounds with lower frequencies for hi-fi soundscapes and melodic, low-pitched sounds for lo-fi soundscapes at higher speeds. They favored melodic, reliable, and futuristic tones for car sounds, avoiding overly epic sounds that could interfere with driving. Emphasizing low and mid-frequencies created a sense of grounding. This research enhances electric vehicle technology and fosters a more harmonious interaction between Electric Vehicles and urban environments. Keywords: Acoustic Vehicle Alerting System, Electric Vehicles, Soundscapes, Sound Design, User Experience, Noise Pollution, Pedestrian Safety, Future Urban Soundscapes, Adaptive AVAS.